Effect of Sediment Feeding on Live-Bed Scour around Circular Bridge Piers - Firat Gumgum; Mehmet Sukru Guney (Salehan Institute of Higher Education, 2021)
The effect of sediment feeding was investigated in the case of live-bed scour around circular bridge piers under flood waves to provide contributions for future experimental procedures. Circular piers of three different diameters were tested in a long rectangular flume containing uniform sediment layer 25 cm thick, by generating 7 different triangular hydrographs with different durations ranging between 6 and 20 minutes and the peak discharges varying from 18 to 38 L/s. Experiments were first conducted without sediment feeding and total load was collected at predetermined time intervals. Then the same experiments were performed by feeding with the same amount of collected sediment. Time dependent scour depths were measured using UVP. Bed degradation was also determined by using an empirical equation existing in the literature. It was found that feeding with the rates equal to the transported ones did not significantly change the scour depth and total sediment load within the limits of the experiments. No significant bed degradation was observed, except at the upstream end. It was revealed that the sediment feeding may not be required in the experiments where temporal evolution of the scour depth is studied in a sufficiently long flume containing sufficient sediment. Doi: 10.28991/cej-2021-03091699 Full Text: PDF